Fiscal income inequalities and efficiency: evidence from Brazilian municipalities - Bernardo Furtado (European Regional Science Association (ERSA), 2012)
Distribution of fiscal income among municipalities – which are constitutionally federal official entities in Brazil - is highly unequal. Given conurbation processes and intense urbanization in the second half of the past century, some municipalities concentrate resources and quality public services whereas neighboring municipalities harbor low-income workers who have to commute back to employment opportunities. As a result, urban landscape in Brazil is far from homogeneous displaying ruptures in level of poverty, criminality, access to transportation networks and leisure activities, among access to other public goods. Given this context, this paper has a threefold objective. Firstly, it identifies the magnitude of these fiscal income inequalities by municipalities using exploratory spatial analysis and detailed fiscal information for 5212 municipalities out of 5565 ones in Brazil. Secondly, this paper describes and characterizes the pairs of neighboring municipalities with high and low fiscal income vis-à-vis their population's income and educational skills. Finally it tests the efficiency of public services offer using Data Envelopment Analysis (DEA). In order to do so, level of expenditures in health services per capita is used as input compared to quantity of health basic attention level services provided. This is done for the sample of extreme pairs of municipalities with high and low fiscal income per capita. Thus, this paper highlights two cumulative issues that municipalities as institutions have to face in order to provide quality service to its citizens: raw resources availability compared to need of inhabitants and efficiency to transform those resources into services. Preliminary results indicate that there are a large number of pairs of municipalities in which one of them concentrates income resources and the other low-income workers with low educational skills. Nevertheless, level of fiscal income does not seem to influence the efficiency of health services provided by municipalities. Therefore, we can provide two practical public policy recommendations to be enforced based on the results: a) better equalization of fiscal income to locations where there are concentration of inhabitants (rather than to locations where there is concentration of economic activity) and b) suggestion of exchange of experiences from successful efficiency programs that have enabled a limited number of municipalities to transform income into quality health public services.
Keywords: 330